Brand assets and pay fairness as two routes to enhancing social capital in sales organizations. Issue 2 (3rd April 2018) - Rouziou, Maria; Dugan, Riley; Rouziès, Dominique; Iacobucci, Dawn
ABSTRACT: A growing body of research in sales highlights the importance of intrafirm relationships. Indeed, sales executives are encouraged to manage internal relationships within their sales force to facilitate high levels of performance. In this research, we examine the concept of social capital – its antecedents and consequences – in the context of a B2B sales organization. In particular, we conceptualize and test two alternative means of enhancing a salesperson's social capital: the impact of branding and perceptions of pay fairness. We then demonstrate how social capital embedded in sales-force relationships can be leveraged through job satisfaction and used to increase sales performance.